POSITION AND ROLE OF DIGITAL MONEY IN THE ECONOMY MACRO PERSPECTIVE OF ISLAMIC VS CONVENTIONAL ECONOMICS - Samsudin; M. Shabri Abd. Majid; Isnaini Harahap (RADJA PUBLIKA, 2024)
The development of information technology has given birth to an innovation in the financial system, namely digital money (cryptocurrency). Conventional economics sees digital money as a tool to improve efficiency, financial access and economic growth. However, there are concerns regarding financial stability, regulation, and potential abuse. On the other hand, Islamic economics has different principles. expand_more Digital money must be sharia-compliant, such as the prohibition of riba, gharar, and maysir. This poses its own challenges in adopting digital money in the Islamic economic framework. This study aims to explore and analyze the position and role of digital money in the economy from Islamic and conventional macroeconomic perspectives, and identify its implications for the global economy. It is hoped that this research can provide insights into the integration of digital money in different economic systems and how to utilize this technology to achieve more inclusive and sustainable economic goals.